THE USE OF METHODS OF ADMINISTRATIVE ANALYSIS FOR DIAGNOSING THE QUALITY COMPONENTS OF THE INTELLIGENT MANAGEMENT SYSTEM OF COMPETITIVENESS OF OIL AND GAS INDUSTRY - Stankovska , I. M. (The actual problems of regional economy development, 2016)
The article explores the use of fdministrative analysis techniques to diagnose quality components of the intelligent competitiveness management system of enterprises of the oil and gas industry. In the article clarified the concept of "quality" and "quality management system", оffered used industry standards to identify the characteristics of qualitys links of the intelligent competitiveness management system. To account for the specifics of the oil and gas industry in the formation of the quality characteristics of the system of competitiveness management of the enterprise is proposed to use relevant international standards of quality. For diagnosing quality of the management system competitiveness of the proposed list of methods administrative analysis. Attention is accented on the necessity of considering the peculiarities of the formalized and non-formalized parts of the system of competitiveness management. JEL: M 20